Non-volatile electric field-mediated magnetic anisotropy in CoZr/ PMN-PT structure - Wang, Zhiling; Zhu, Dengyu; Liu, Fufu; Zhou, Cai; Jiang, Changjun (Frontiers in Materials, 2023)
Introduction: Although electric field mediated the magnetic anisotropy in ferromagnetic/ferroelectric structure have an intense report, the angle between the magnetic uniaxial anisotropy and strain anisotropy influencing the rearrangement of the magnetic moment has not well investigated. Methods: Keithley 2410 direct current power supply was used to provide voltage through the Cu wires. Static magnetic properties of CoZr layer were measured through VSM (MicroSense EV9). Dynamic magnetic properties were obtained by FMR (JEOL JES-FA 300 spectrometer, power of 1-mW, X-band at 8.969 GHz). Results and Discussion: Electric field-mediated, room-temperature magnetic anisotropy of CoZr/Pb(Mg1/3Nb2/3)O3–PbTiO3 (PMN–PT) structures, in which easy axis of CoZr layer along either direction of [01-1] or [100] of PMN–PT, was investigated. Measured with vibrating sample magnetometer, for [01-1] easy-axis direction sample, when an electric field was applied, these directions of easy axis and hard axis remains unchanged. However, for [100] easy-axis direction sample, these directions of easy axis and hard axis were changed obviously with applying electric field, attributable to the competition between magnetic uniaxial anisotropy of CoZr layer and piezostrain anisotropy of PMN-PT substrate. Nevertheless, change of the resonance magnetic field with electric field–measured by ferromagnetic resonance–exhibited non-volatile behavior, which possibly indicates magnon-driven magnetoelectric coupling existing in CoZr/PMN–PT structures.